Protein kinase C epsilon activation regulates proliferation, migration, and epithelial to mesenchymal-like transition in rat Schwann cells - Mohamed, Tasnim; Colciago, Alessandra; Montagnani Marelli, Marina; Moretti, Roberta Manuela; Magnaghi, Valerio (Frontiers in Cellular Neuroscience, 2023)
Introduction Protein kinase type C-ε (PKCε) plays an important role in the sensitization of primary afferent nociceptors, promoting mechanical hyperalgesia. In accordance, we showed that PKCε is present in sensory neurons of the peripheral nervous system (PNS), participating in the control of pain onset and chronification. Recently, it was found that PKCε is also implicated in the control of cell proliferation, promoting mitogenesis and metastatic invasion in some types of cancer. However, its role in the main glial cell of the PNS, the Schwann cells (SCs), was still not investigated. Methods Rat primary SCs culture were treated with different pharmacologic approaches, including the PKCε agonist dicyclopropyl-linoleic acid (DCP-LA) 500 nM, the human recombinant brain derived neurotrophic factor (BDNF) 1 nM and the TrkB receptor antagonist cyclotraxin B 10 nM. The proliferation (by cell count), the migration (by scratch test and Boyden assay) as well as some markers of SCs differentiation and epithelial-mesenchymal transition (EMT) process (by qRT-PCR and western blot) were analyzed. Results Overall, we found that PKCε is constitutively expressed in SCs, where it is likely involved in the switch from the proliferative toward the differentiated state. Indeed, we demonstrated that PKCε activation regulates SCs proliferation, increases their migration, and the expression of some markers (e.g., glycoprotein P0 and the transcription factor Krox20) of SCs differentiation. Through an autocrine mechanism, BDNF activates TrkB receptor, and controls SCs proliferation via PKCε. Importantly, PKCε activation likely promoted a partial EMT process in SCs. Discussion PKCε mediates relevant actions in the neuronal and glial compartment of the PNS. In particular, we posit a novel function for PKCε in the transformation of SCs, assuming a role in the mechanisms controlling SCs' fate and plasticity.